Radix of Prophetic Communicology: Ethical Perspective of the Qur'an - Muhtadi, Asep Saeful (STAI AL-FALAH CICALENGKA, 2021)
Communication ethics has a signal footing (cue) in the ethical concepts of the Qur'an. These cues show instructions on how to build smarter and more civilized communication ethics which are more popularly called